2013
DOI: 10.1017/s0007114513001931
|View full text |Cite
|
Sign up to set email alerts
|

The Mediterranean diet in relation to mortality and CVD: a Danish cohort study

Abstract: The aim of the present study was to determine whether the Mediterranean Diet Score (MDS) is associated with reduced total mortality, cardiovascular incidence and mortality in a Danish population. Analyses were performed on 1849 men and women sampled during the 1982 -83 Danish MONICA (MONItoring trends and determinants of Cardiovascular disease) population study, whose diet was assessed by means of a validated 7 d food record. The adherence to a Mediterranean dietary pattern was calculated by three different sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 39 publications
4
84
0
2
Order By: Relevance
“…In agreement with our results, a Mediterranean dietary pattern was inversely associated with all‐cause mortality in the US Multiethnic Cohort,37 the US National Institutes of Health–AARP Diet and Health Study,38 Spanish cohorts,32, 39 an Italian cohort,40 the UK‐based EPIC (European Prospective Investigation of Cancer)–Norfolk study,41 a Danish cohort,42 and a cohort of elderly European men and women 43. However, there was no association of a Mediterranean‐type diet with all‐cause mortality in the UK‐based Whitehall II study 33.…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with our results, a Mediterranean dietary pattern was inversely associated with all‐cause mortality in the US Multiethnic Cohort,37 the US National Institutes of Health–AARP Diet and Health Study,38 Spanish cohorts,32, 39 an Italian cohort,40 the UK‐based EPIC (European Prospective Investigation of Cancer)–Norfolk study,41 a Danish cohort,42 and a cohort of elderly European men and women 43. However, there was no association of a Mediterranean‐type diet with all‐cause mortality in the UK‐based Whitehall II study 33.…”
Section: Discussionsupporting
confidence: 90%
“…A similar result was found by a meta-analysis of 50 studies involving 534,906 individuals, assessing effects of the diet on components of the metabolic syndrome [49]. A recent study in a Danish cohort found that adherence to the Mediterranean diet was associated with reduced all-cause mortality and cardiovascular events and mortality, but not stroke [52]. …”
Section: Mediterranean Dietsupporting
confidence: 74%
“…[38][39][40] Accordingly, we have previously published a paper based on a version of the MDS adapted to the food frequency data used in the IDEFICS study to assess children's usual diets 29 in relation to their weight status. In the present paper, we used data collected in the same study using another methodology, 24 h recall data, which could provide more detailed food and nutrient data but which is less useful than the FFQ for considering associations with health-related outcomes such as body weight.…”
Section: Discussionmentioning
confidence: 99%